Tennis Collector Ball Machine - Azman, Muhammad Aizat Shahmin; Ubin, Aizan (Evolution in Electrical and Electronic Engineering, 2023)
During training sessions, it is typical for tennis players to hit many tennis balls across the court. Collecting these balls manually can be time-consuming and tedious. This work intends to create an automatic tennis ball collector that relieves players of the stress of manual retrieval, allowing them to concentrate on training. The tennis ball picker machine uses vision-based technology, object-tracking techniques, and digital image processing to detect and track tennis balls. By assessing their colour, shape, and size attributes, the system properly recognizes the tennis balls' location on the court. The image sensor Pixy 2.1 CMUcam5 feeds the machine with the ball's position coordinates, enabling accurate movement control. The Pixy 2.1 camera's input of the machine's coordinates ensures efficient navigation towards the desired ball spot. Additionally, infrared sensors are added to identify tennis balls, which will be shown in the Blynk app the counting ball was collected, while the Pixy2 CMUcam5 camera sensor expands the detection range to 100 cm. A combination of an Arduino Uno microprocessor and an ESP8266 V3 allows the machine to retrieve a tennis ball in less than seven seconds every 20 cm distance of the ball. Tennis players who wish to improve their skills through concentrated practice sessions will find the automatic collector tennis ball machine to be an invaluable aid. It eliminates the requirement for manual ball collection, allowing for longer training times. The machine was tested on the Tennis Court UTHM to ensure that it worked properly in a real-world situation. Life is made easier by technological advances such as IoT system that was implemented in the work. Manual collector ball machines are a cost-effective option in instances where funds are limited. The decision between manual and automatic collector ball machines is ultimately determined by the individual's needs, budget, and preferences. Both choices have significant advantages and disadvantages, and players can choose the most appropriate option based on their needs.